Influence of long-term integrated nutrient management on soil properties, nutrient balance and productivity of rice–wheat cropping system in Central Indo-Gangetic plains - KUMAR, NEERAJ; SINGH, A.K.; BAHADUR, RAJ; KUMAR, ROBIN; ARORA, SANJAY; MEHTA, VISHAL; BAHELIYA, A.K.; KUMAR, DHARMENDRA (Journal of Soil and Water Conservation, 2024)
The present investigation was initiated in 1984 at the agronomy research farm of Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, Uttar Pradesh, India, to study the long-term (35 years) effect of integrated nutrient management on crop productivity, soil properties, nutrient uptake and nutrient balance under a rice-wheat cropping system. The study aimed to assess the impact of different combinations of inorganic fertilizers (NPK) and organic sources (such as farmyard manure, wheat cut straw, and Sesbania aculeata green manure) on crop productivity, nutrient uptake, soil nutrient balance and fertility under the rice-wheat system. Twelve treatment combinations were tested, including variations of fertilizer nutrients N, P, and K, either alone or in combination with different organic sources to replace 25% to 50% of N through farmyard manure, wheat cut straw, and Sesbania aculeata green manure (GM). Organic sources positively influenced soil properties, nutrient availability, and yields of rice and wheat. Integrated nutrient management led to increased soil organic carbon content, available nitrogen, phosphorus and potassium in treated plots compared to inorganic fertilizer-treated plots. Over three decades, the most significant changes were observed in T10 (Rice: 50% NPK + 50% N (GM) in Kharif and 100% recommended NPK dose through fertilizer in Rabi) compared to chemically fertilized plots (T5) during the initial years. Notably, higher rice and wheat yields were initially achieved with 100% NPK from chemical fertilizers alone than with various combinations of inorganic and organic fertilizers. Furthermore, soil enrichment was evident in terms of DTPA-extractable Zn, Cu, Fe, and Mn content, with notable improvements due to the addition of organic sources. The study emphasized that a balanced approach, integrating chemical fertilizers with organic manures over the long term, improves soil properties, enhances nutrient status, crop productivity, and ultimately contributes to soil sustainability.